2016
DOI: 10.3390/min6010008
|View full text |Cite
|
Sign up to set email alerts
|

Ciriottiite, Cu(Cu,Ag)3Pb19(Sb,As)22(As2)S56, the Cu-Analogue of Sterryite from the Tavagnasco Mining District, Piedmont, Italy

Abstract: Abstract:The new mineral species ciriottiite, ideally Cu(Cu,Ag) 3 Pb 19 (Sb,As) 22 (As 2 )S 56 has been discovered in the Tavagnasco mining district, Piedmont, Italy, as very rare black metallic tubular crystals, up to 150 µm in length, associated with Bi sulfosalts and arsenopyrite. Its Vickers hardness (VHN 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moëlo et al (2012) reported the crystal structure of two complex Ag-Pb sulfosalts, sterryite and parasterryite, Cu(Ag,Cu) 3 Pb 19 (Sb,As) 22 (As 2 )S 56 and Ag 4 Pb 20 (Sb,As) 24 S 58 , respectively. These two minerals, along with ciriottiite, Cu(Cu,Ag) 3 Pb 19 (Sb,As) 22 (As )S (Bindi et al 2016a), are expanded derivative of owyheeite, Ag 3 Pb 10 Sb 11 S 28 (Moëlo et al 1984;Laufek et al 2007), a rare Ag-Pb sulfosalt showing an OD nature (Makovicky and Olsen 2015). Figure 46 shows some structural features of sterryite and parasterryite.…”
Section: Other Zinkenite-related Complex Sulfosaltsmentioning
confidence: 98%
“…Moëlo et al (2012) reported the crystal structure of two complex Ag-Pb sulfosalts, sterryite and parasterryite, Cu(Ag,Cu) 3 Pb 19 (Sb,As) 22 (As 2 )S 56 and Ag 4 Pb 20 (Sb,As) 24 S 58 , respectively. These two minerals, along with ciriottiite, Cu(Cu,Ag) 3 Pb 19 (Sb,As) 22 (As )S (Bindi et al 2016a), are expanded derivative of owyheeite, Ag 3 Pb 10 Sb 11 S 28 (Moëlo et al 1984;Laufek et al 2007), a rare Ag-Pb sulfosalt showing an OD nature (Makovicky and Olsen 2015). Figure 46 shows some structural features of sterryite and parasterryite.…”
Section: Other Zinkenite-related Complex Sulfosaltsmentioning
confidence: 98%